Modulation of S100 and smooth muscle actin-Î± immunoreactivity in the wall of aorta after vitamin D administration in rats with high fat diet - Wagih, Heba Mohamed; Hashem, Hala Elwy; Hassan, Zienab Abdelrehem; Algaidi, Sami Auda (Cellular and Molecular Biology, 2018)
High fat diet is a risk factor for the development of atherosclerosis. Hence, research studies are important to understand the cellular and molecular mechanisms of atherosclerosis pathogenesis. The current study was conducted to evaluate the role of vitamin D in modulation of aortic histopathological, immunohistochemical alterations and biochemical changes induced by high fat diet in male albino rats. Forty adult rats were divided into three major groups; group I (control), group II (High fat diet) and group III (High fat diet with vitamin D). At the end of the experiment, blood cholesterol and triglycerides were determined. Aortic arches specimens were collected for histopathological study and immunohistochemical staining. Aorta of high fat diet group showed intimal thickening with vacuolated endothelial cells. The tunica media showed areas of fibrosis and irregular vacuolated smooth muscle cells. Many inflammatory cells were detected in the tunica adventitia. Significant reduction in area percentage of smooth muscle actin-Î± (SMA-Î±) immunoreactivity and increase in number of S100 positive dendritic cells (DCs) with significant increase in serum cholesterol and triglycerides were also detected. Concomitant vitamin D supplementation, with high fat diet, showed amelioration in histopathological aortic changes with significant increase in SMA-Î± immunoreactivity and decrease in S100 positive (DCs). However, serum cholesterol and triglyceride showed non-significant decrease after vitamin D supplementation. In conclusion, vitamin D administration ameliorates aortic wall histoopathological changes induced by high fat diet most probably through local modulation of S100 and SMA-Î± immunoreactivity. Hence, vitamin D could be suggested as a protective agent against aortic atherosclerotic changes.